Chasing shadows [large type] - Austin, Lynn N. (Center Point Large Print, 2022)
"The lives of three women are instantly changed when the Nazis invade the neutral Netherlands, forcing each into a complicated dance of choice and consequence. Lena is a wife and mother who farms alongside her husband in the tranquil countryside. Her faith has always been her compass, but can she remain steadfast when the questions grow increasingly complex and the answers could mean the difference between life and death? Lena's daughter Ans has recently moved to the bustling city of Leiden, filled with romantic notions of a new job and a young Dutch police officer. But when she is drawn into Resistance work, her idealism collides with the dangerous reality that comes with fighting the enemy. Miriam is a young Jewish violinist who immigrated for the safety Holland offered. She finds love in her new country, but as her family settles in Leiden, the events that follow will test them in ways she never imagined. The Nazi invasion propels these women onto paths that cross in unexpected, sometimes heartbreaking, ways. Yet the story that unfolds illuminates the surprising endurance of the human spirit and the power of faith and love to carry us through"--